Initial Steps to Engineer Coproheme Decarboxylase to Obtain Stereospecific Monovinyl, Monopropionyl Deuterohemes - Michlits, Hanna; Valente, Nina; Mlynek, Georg; Hofbauer, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
The oxidative decarboxylation of coproheme to form heme b by coproheme decarboxylase is a stereospecific two-step reaction. In the first step the propionate at position two (p2) is cleaved off the pyrrole ring A to form a vinyl group at this position. Subsequently the propionate at position four (p4) on pyrrole ring B is cleaved off and heme b is formed. In this study, we attempted to engineer coproheme decarboxylase from Corynebacterium diphtheriae to alter the stereospecificity of this reaction. Introducing a tyrosine residue in proximity to the propionate at position 4, we were able to create a new radical center in the active site. However, the artificial Tyr183• radical could not be shown to catalyze any decarboxylation.